Sapientia astrologica : astrology, magic and natural knowledge, ca. 1250-1800.: astrology, magic and natural knowledge, ca. 1250-1800. Medieval structures (1250-1500): conceptual, institutional, socio-political, theologico-religious and cultural / I, ([2019]) - Rutkin, H. Darrel
No abstract available